Multiterritorialidade no Distrito de Itapina, Colatina: Espírito Santo - Tesch, Arleida Lemke (2018)
This dissertation analyses the evolution of settlement, the coffee economy, the transport infrastructure and its interrelations between the multi-territoriality materialised in Itapina’s landscape. It looks especially into the period between 1906 – the arrival of rails alongside with Rio Doce’s riverbanks – and 2016 – the end of the city management, which consolidates Itapina’s urban nucleus as a heritage area and a Protection Area of Cultural Environment. It highlights the importance of Francisco Vieira de Carvalho Milagres’ Fazenda da Serra in the settlement of Itapina’s urban nucleus surroundings. It identifies Aldeamento Laje’s location and the presence of Munhagerunsand and Nac-Nuncs indigenous people at Ribeirão Laje’s mouth, tributary of Rio Doce and SPI’s action aiming at minimizing the conflicts, which occur between the indigenous people and the settlers. It highlights the existing connections between communication channels used by muleteers with the railway and river navigation, especially at Rio Doce. These channels are later on materialised in roads and highways. It emphasizes the Vitória-Minas Railway’s history and its importance to the trading post established at Itapina’s urban nucleus. It pinpoints that the rise and climax of economic life in Itapina occurs in the years between 1920 and 1950 and the decay in the years between 1960 and 1970, when coffee is eradicated in Espírito Santo and in Brazil. By using several academic work, such as books, articles, dissertations, thesis, study analysis, reports, diagnostics, newspapers, and magazines about the focus adopted in the research produced by government bodies and linked to them and that approaches the theme and temporal focus of the research, it analyses the process of the territory occupation through its settlement, the implementation of transport means, the coffee cultivation at Itapina’s nucleus surroundings which establishes itself as a combined and continuous dynamics of multi-territoriality expressed in the territorialisation and in the deterritorialisation of the individual, social group, and the State which build their multi-territories by integrating the cultural, economic, and political experience in regards to the space. The results emphasise the reasons why the urban nucleus economic life decays, highlight that the brief moment of rise and decay which is materialised in the space/territory as a legacy preserved through the heritage listing of Itapina’s Protection Area of Cultural Environment which is organised through sectors at Itapina’s Historical Site, demonstrate that the population, represented in the research, attribute value to territories in PACE, and these territories correspond to objects, events, constructions, landscape elements, and the values which are in continuous reconstitution.